PENYULUHAN TENTANG PENGELOLAAN REKAM MEDIS DAN INFORMASI KESEHATAN DI PUSKESMAS DELI TUA KABUPATEN DELI SERDANG - Ahmad Fatikhus Sholikh; Elmina Tampubolon; Ripai Siregar; Yerni Mariani Sitompul (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The medical record is one of the bases for assessing the quality of medical services In a hospital or clinic. Medical record officers have big duties and responsibilities in maintaining the integrity of medical records. It is hoped that medical record officers will really know the ins and outs of medical records in a comprehensive and in-depth manner. The purpose of this study was to determine how the management of the medical record system at Deli Tua Health Center.. This research was conducted using qualitative research methods with in-depth interviews with informants. The subjects in this study were medical record officers, heads of public health centers, doctors and nurses. The results showed that the unit of medical records at Deli Tua Community Health Center still did not meet the standards both in terms of quality and quantity, but in terms of understanding, medical record officers at Deli Tua Health Center had a fairly good understanding of medical records. The facilities and infrastructure in the medical records of the Deli Tua Health Center are also incomplete and limited. In the implementation of activities, it has been carried out in accordance with the SPO, so that cooperation between officers in individual health efforts is also considered good, as well as the flow of medical records has been running according to the SPO.